2022
DOI: 10.1002/ijc.33925
|View full text |Cite
|
Sign up to set email alerts
|

Composite dietary antioxidant index and the risk of colorectal cancer: Findings from the Singapore Chinese Health Study

Abstract: Colorectal cancer (CRC) is a major contributor to cancer death globally. Several studies showed some protections by certain individual dietary antioxidants against CRC development. Epidemiologic data on the composite dietary antioxidant index (CDAI) in relation to CRC risk are sparse. Using the Singapore Chinese Health Study, an ongoing prospective cohort consisting of 61 321 cancer‐free participants aged 45 to 74 years at baseline, a food‐based CDAI was calculated according to a previously established and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 52 publications
(111 reference statements)
2
49
0
Order By: Relevance
“…Paragomi et al showed that the overall levels of dietary antioxidants decreased the risk of pancreatic cancer [ 34 ]. Yu et al reported an inverse relationship between CDAI and the risk of colorectal cancer, suggesting that antioxidants might reduce the incidence of colorectal cancer in the population [ 32 ]. Besides, dietary antioxidants were also reported to be associated with mortality, although not consistently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paragomi et al showed that the overall levels of dietary antioxidants decreased the risk of pancreatic cancer [ 34 ]. Yu et al reported an inverse relationship between CDAI and the risk of colorectal cancer, suggesting that antioxidants might reduce the incidence of colorectal cancer in the population [ 32 ]. Besides, dietary antioxidants were also reported to be associated with mortality, although not consistently.…”
Section: Discussionmentioning
confidence: 99%
“…The CDAI was developed to evaluate and reflect the overall impact of dietary antioxidants on health. Previous studies found that high CDAI was related to a decreased risk of various types of cancer [ 32 34 ]. To our knowledge, the relationship between CDAI and plasma levels of Klotho has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because of their critical role in most diets worldwide, interest in the health effects of dietary total antioxidant capacity (TAC) is increasing. Previous studies found an inverse association between CDAI and cancer risk (8,9,11); however, similar efforts at cardiovascular mortality among the general population have not yet been conducted.…”
Section: Introductionmentioning
confidence: 94%
“…Including multiple dietary antioxidants such as manganese, zinc, selenium, and vitamins A and C, the Composite Dietary Antioxidant Index (CDAI) serves as a summary score for reflecting the antioxidant profile of individuals ( 8 , 9 ). CDAI was constructed in accordance with their aggregate anti-inflammatory impact based on markers like tumor necrosis factor-α and interleukin-1β ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CDAI was developed based on its combined effect on anti-inflammatory effects based on the pro-inflammatory markers Tumor Necrosis Factor-α (TNF-α) and Interleukin-1β (IL-1β), which are associated with many health outcomes, including depression, all-cause mortality, colorectal cancer, etc. (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%